Factors related to stress fracture after unicompartmental knee arthroplasty - Masamichi Yokoyama; Yasuhiro Nakamura; Makoto Egusa; Hideyuki Doi; Toru Onishi; Koji Hirano; Motoyuki Doi (Elsevier, 2019)
Background/objective: Unicompartmental knee arthroplasty (UKA) is a low-invasive knee surgery that enables early recovery. Stress fracture of the medial tibial plateau (MTP) is a complication of UKA that prolongs treatment once it has occurred. We investigated factors affecting its occurrence. Methods: The study subjects were 167 patients who underwent fixed-bearing UKA between 2009 and 2016 (45 men and 122 women of mean age 77 years, including 134 with osteoarthritis of the knee and 33 with spontaneous osteonecrosis). We measured bone mineral density, installation angle of the tibial component, and leg alignment in those patients who developed stress fracture within 3 months after UKA. Results: Stress fracture did not occur in 155 patients (N group, 45 men and 110 women) and did occur in 12 (SF group, 12 women). The bone mineral density (BMD) of the proximal femur was significantly lower in the SF group, indicating that bone fragility may have contributed to stress fractures at this site. There was no significant difference in the preoperative tibio-femoral angle (TFA), however, postoperative TFA was larger and the magnitude of the change in the valgus direction (ΔTFA) was smaller in the SF group. Discussion: In usual UKA for medial compartment, the leg is more extroverted postoperatively than preoperatively, and leaving the knee in the genu varus position, which places a greater load on the tibial component, may raise the risk of stress fracture. Although there was no difference between the two groups in the varus angle of the tibial component, in a scatter plot of postoperative TFA and the installation angle of the tibial component members of the SF group were concentrated in the region of high TFA and low varus angle. Varus of the leg and a low varus angle of the tibial component may thus be factors in the occurrence of stress fracture. Conclusion: Our results suggested that low BMD in the affected femur, large postoperative TFA, and a combination of large postoperative TFA and small varus angle of the tibial component may contribute to stress fracture of the MTP following UKA. Keywords: Unicompartmental knee arthroplasty, Complication, Stress fracture